Principles of Stress Granules Revealed by Imaging Approaches - Van Treeck, Briana (Cold Spring Harb Perspect Biol, 2019)
Eukaryotic cells contain a large number of RNA–protein assemblies, generically referred to as ribonucleoprotein (RNP) granules. Such RNP granules include stress granules and P-bodies in the cytosol and the nucleolus, Cajal bodies, and paraspeckles in the nucleus. A variety of imaging approaches have been used to reveal different components, structural features, and dynamics of RNP granules. In this review, we discuss imaging approaches that have been used to study stress granules and the insights gained from these experiments. A general theme is that these approaches can be transferred to other RNP granules to examine similar aspects of their composition, ultrastructure, dynamics and control.